2019
DOI: 10.2147/ppa.s225561
|View full text |Cite
|
Sign up to set email alerts
|

<p>Illness perception and sense of well-being in breast cancer patients</p>

Abstract: PurposeThe objective of the study was to explore breast cancer patients’ illness perception, its relationship to perceived sense of well-being, and the role of perceived social support.MethodsWomen with diagnosed breast cancer were recruited from the two university hospitals in South Korea between January and April 2018. The questionnaires included the Illness Perception Questionnaire-Revised (IPQ-R) and the Functional Assessment of Cancer Therapy for Breast cancer (FACT-B). A total of 321 participants’ data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 48 publications
(69 reference statements)
5
25
0
Order By: Relevance
“…More threatening emotional representations of COVID-19 correlated negatively with psychological well-being. Regarding COVID-19, threatening emotional representations were associated with attitudes and intentions towards adherence to preventive behaviors [17,20], and therefore, with less psychological well-being [17].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…More threatening emotional representations of COVID-19 correlated negatively with psychological well-being. Regarding COVID-19, threatening emotional representations were associated with attitudes and intentions towards adherence to preventive behaviors [17,20], and therefore, with less psychological well-being [17].…”
Section: Discussionmentioning
confidence: 97%
“…The role of less threatening emotional representation regarding COVID-19 is also critical. In cases of chronic disease, threatening illness perceptions were systematically associated with attitudes and intentions towards adherence to preventive behaviors [17,18] and, the latter towards psychological well-being [17]. During the current pandemic, Aqeel et al [19] found a significant negative relationship between distress, mental health, and illness perception.…”
Section: Illness Perceptions and Emotional Reactionmentioning
confidence: 99%
“…This marker combines cognitive, emotional, quality of life and precariousness items and at the time of diagnosis, a larger effect size of the global Z score of these items may predict the patient to belong to a PP trajectory. The analysis of baseline items z-scores for cognition, emotion and quality of life, indicates a number of characteristics of the PP trajectory perspective—negative illness perception [ 55 , 56 ], anxiety [ 57 , 58 , 59 , 60 , 61 ], feeling guilty about cancer [ 40 , 62 ] and poorer quality of life [ 52 , 53 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other three dimensions assess positive perceptions as treatment control, personal control and illness coherence, with higher scores indicating more positive beliefs. The questionnaire was used to measure illness perceptions among patients with different diseases, including cancer with good psychometric properties [34][35][36]. The Cronbach's alpha coefficients for the translated Romanian version ranged between 0.68 and 0.85 for the 9 dimensions.…”
Section: Methodsmentioning
confidence: 99%